PENERAPAN MEDIA BELAJAR PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI PENGGOLONGAN MAKHLUK HIDUP SISWA KELAS III SEKOLAH DASAR NEGERI MANDALASARI 2 PANDEGLANG - Robiatul Munajah (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
Learning games are used to create an exciting atmosphere and this will encourage the acceleration of learning. Specifically in science learning by using a constructivist approach encourages students to increase their courage and foster collaboration in trying to find solutions to their own ways and find complex information so that students automatically re-establish new understanding to overcome problems. Based on the results of research students' learning activities progressed in several activities namely asking in the first cycle 59% rose to 63.63%, answered from 68% to 72.72%, but in refuting activities 9% did not increase and the activity of expressing opinions increased from 13.63% to 18% however, still in the lack category. From the test results during the research it can be concluded that the application of puzzles with constructivist approaches in science learning can improve students' ability to understand the concept of classifying living things. This is evidenced by the two times the implementation or cycle obtained the average value of the test results of each cycle that always increases. The value obtained in the first cycle of pretest meetings reached an average of 48.4 then in the post-test it rose to 60.64, this indicates an increase of 12 points. Then the second meeting reached 63 pretest and posttest reached 70.20. This shows that all students who follow the second cycle have succeeded in exceeding the limits of mastery learning.